An Orthogonal Waveform for Fully Polarimetric MIMO-SAR - Rommel, Tobias; Younis, Marwan; Krieger, Gerhard (IEEE Radar Conference (RadarCon), 2014)
Synthetic aperture radar (SAR) with multiple transmit and receive channels (MIMO-SAR) has a higher flexibility and an improved efficiency compared to a conventional SAR system with a single channel. The multiple receive channels can be used, among other things, to increase the swath width at constant azimuth resolution or to suppress spatial interferences. However, multiple transmit channels, which transmit simultaneously in the same frequency band provide currently a challenge. Therefore, in this paper a modified Chirp waveform is introduced which extends in combination with digital beam-forming (DBF) on receive the orthogonality condition to another degree of freedom, thus allowing perfect orthogonality. Furthermore, the hardware design of the MIMO-Radar Demonstrator, a multi-channel measurement system for radar and SAR applications is depicted. The shown measurement result demonstrates the possibility of obtaining all four parameters of the scattering matrix at the same time by transmitting orthogonal waveforms in different polarizations.
DLR Import::2019-04-03